FENOLOGI DAN TINGKAT KEMASAKAN BENIH MENGKUDU (Morinda citrifolia L.) - Rosdiana Ngitung; Arsad Bahri (Universitas Tadulako, 2008)
The aim of the research was to determine the physiological ripen time of mengkudu seed based on penology study. The study was conducted in the Green House and Experimental Farm of Jurusan Biologi FMIPA Universitas Negeri Makassar (UNM). Penological observation was done since the beginning of flowering until the fruit formation was completed and mature. The experiment conducted used three trees, in each tree three branches with all their blossoming flowers were labeled for observation. Therefore, there were 3 x 3 = 9 branches including their flowers were observed for the flower transformations and development, fruit formation and fruit maturity stages. There were three stages found for the mengkudu fruit to reach maturity. Such stages were stage M-1 (perfectly fruit formation), stage M-2 (morphological mature), and stage M-3 (physiological mature). Based on visual observation, the exocarp changes were followed by mesocarp (fruit meat) and endocarp (seed skin) transformations.